2009
DOI: 10.3858/emm.2009.41.12.098
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Streptomyces bacteriophage φC31 integrase system to prevent post integrative gene silencing in pulmonary type II cells

Abstract: AbstractφC31 integrase has emerged as a potent tool for achieving long-term gene expression in different tissues. The present study aimed at optimizing elements of φC31 integrase system for alveolar type II cells. Luciferase and β-galactosidase activities were measured at different time points post transfection. 5-Aza-2'deoxycytidine (AZA) and trichostatin A (TSA) were used to inhibit DNA methyltransferase and histone deacetylase complex (HDAC) respectively. In A549 cells, expression of the integrase using a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Promoter methylation is a powerful cause for transgene silencing in vitro and in vivo due to methylation of CpG dinucleotide by DNA methyltransferase enzymes. One solution to this problem is the removal of the CpG motifs in the promoter and bacterial backbone, which leads to stable, uniform expression of integrative gene in the genome of target cells 27 . Using CpG-free EF1α promoter, we observed that EGFP expression level was higher than that of wild-type EF1α and CMV promoters from BF10 site in blastocysts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation is a powerful cause for transgene silencing in vitro and in vivo due to methylation of CpG dinucleotide by DNA methyltransferase enzymes. One solution to this problem is the removal of the CpG motifs in the promoter and bacterial backbone, which leads to stable, uniform expression of integrative gene in the genome of target cells 27 . Using CpG-free EF1α promoter, we observed that EGFP expression level was higher than that of wild-type EF1α and CMV promoters from BF10 site in blastocysts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this observation, we constructed several vectors with CMV‐derived promoters (Figure ) and monitored their expression for more than 1 month to validate them for long‐term gene expression in vitro . Although all integrative vectors maintained gene expression for more than 1 month, we decided to use pattB‐CAG‐IDUA in all of our in vivo experiments because the hybrid CMV promoter CAG has been used in several in vivo gene transfer experiments without observing gene silencing , whereas the pure CMV promoter is typically silenced . Additionally, Aronovich et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, this increased recombination activity has not been replicated. Rather, two recent studies have concluded that adding an NLS to the C-terminal end of f C31 integrase does not signi fi cantly increase activity, and instead causes a decrease in activity (Aneja et al 2009 ;Woodard et al 2010a ) .…”
Section: F C31 Integrase: Mechanism Of Integration and Optimization Fmentioning
confidence: 99%
“…Using cellular promoters, however, resulted in stable, long-term expression of the integrated transgene (Aneja et al 2009 ) . Thus, whereas it may not be useful to optimize the coding sequence of f C31 integrase or to add a NLS sequence to either end of the protein, it may be advantageous to optimize the donor plasmid by using a cellular promoter for transgene expression.…”
Section: F C31 Integrase: Mechanism Of Integration and Optimization Fmentioning
confidence: 99%
See 1 more Smart Citation